1974
DOI: 10.3109/00016347409156885
|View full text |Cite
|
Sign up to set email alerts
|

Lumbar Epidural Analgesia in Labour

Abstract: Twenty-four full-term nulliparae and their babies were studied. Twelve received lumbar epidural analgesia with bupivacaine (Marcain-adrenalin@) and twelve conventional obstetrical analgesia with meperidine (PetidinaD), chlorpromazine (Hibernalm), nitrous oxide and a pudendal nerve block with prilocaine (Citanestm). The acid-base balance was determined in fetal and maternal blood during labour and in neonatal blood after birth. The newborn infants were placed in incubators after birth and several clinical param… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0
1

Year Published

1977
1977
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(19 citation statements)
references
References 13 publications
(4 reference statements)
1
16
0
1
Order By: Relevance
“…In the newborn infants, determinations of blood gases, acid-base balance, and lactate were made on arterial blood obtained during the first 2 h of life. All results were in accordance with reference values for normal infants reported by other investigators (1, 2,4,7,10,15,16,27,28). Clinical observations during the early neonatal period and the first week of life were all normal.…”
Section: Control Groupsupporting
confidence: 81%
“…In the newborn infants, determinations of blood gases, acid-base balance, and lactate were made on arterial blood obtained during the first 2 h of life. All results were in accordance with reference values for normal infants reported by other investigators (1, 2,4,7,10,15,16,27,28). Clinical observations during the early neonatal period and the first week of life were all normal.…”
Section: Control Groupsupporting
confidence: 81%
“…Table 1 describes the studies that have been included in the meta‐analysis 6–9,14–22 . These include some studies in which old‐fashioned epidural analgesia using local anaesthetic without opioid was used, and others using the more up‐to‐date low dose combinations.…”
Section: Methodsmentioning
confidence: 99%
“…If these potentially adverse intrapartum effects of epidural analgesia were harmful to the baby, this would be reflected in the neonatal acid–base status. Early studies published in 1974, however, reporting funic pH and base excess, suggested that epidural analgesia was associated with reduced fetal/neonatal acidosis and even appeared to protect the fetus from the detrimental effects of a prolonged second stage of labour 6–9 .…”
Section: Introductionmentioning
confidence: 99%
“…81 They showed that epidural analgesia reduced maternal hypocarbia and maternal and fetal metabolic acidosis and lactate, 83 while greatly mitigating the fall in fetal pH that otherwise occurs during the second stage of labour. These favourable findings were largely ignored by all but a few anaesthesiologists.…”
Section: Neonatal Acid-base Statusmentioning
confidence: 98%